Bible and Ecology Rediscovering the Community of Creation - Bauckham, Richard (2009)
In this well-argued and timely book, Bauckham considers the relationship of humans to the rest of creation.He argues that there is much more to the Bible's understanding of this relationship than the mandate of human dominion given in Genesis 1, which has too often been used as a justification for domination and exploitation of the earth's resources. He also critiques the notion of stewardship as being on the one hand presumptuous, and on the other too general a term to explain our key responsibilities in caring for the earth. In countering this, he considers other biblical perspectives, including the book of Job, the Psalms and the Gospels, and re-evaluates the biblical tradition of 'dominion', in favour of a 'community of creation'.With its clear analysis and thought-provoking conclusions, The Bible and Ecology is an essential read for anyone interested in a biblically grounded approach to ecology.